Crystallization behaviors of Ga30Sb70/GeTe nanocomposite multilayer thin films. (14th April 2016) - He, Zifang; Feng, Xiaoyi; Liu, RuiRui; Zhai, Jiwei; Changzhou, Wang
Abstract: The multi-step phase change behaviors in Ga30 Sb70 /GeTe (GS/GT) nanocomposite multilayer films are investigated through in situ film resistance and x-ray diffraction (XRD) measurements as well as transmission electron microscopy (TEM). Analyses of XRD and TEM indicate that the multi-step phase change in GS/GT films results from its unique crystallization mechanism (amorphous-mix crystalline–crystalline). What is more, for single period samples, the thickness of each layer has an obvious influence on multi-step transition performance. In terms of [GS( a nm)/GT( a nm)]1 film configuration, the optimized thickness of each layer should be in the range 50–100 nm. Above all, GS/GT nanocomposite thin films with one period harbor great potential for high-density phase change random access memory applications.